2003
DOI: 10.1016/s0741-5214(02)75333-0
|View full text |Cite
|
Sign up to set email alerts
|

Sustained inhibition of experimental neointimal hyperplasia with a genetically modified herpes simplex virus1 1Competition of interest: none.

Abstract: The virulence-attenuated HSV strain R849 demonstrates selective cytotoxicity for SMC and is capable of sustained inhibition of NIH in an experimental model of vein graft failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 27 publications
0
12
0
1
Order By: Relevance
“…2, 4 Furthermore, we have shown that we are able to modulate intimal hyperplasia in a relevant vein graft model. 17, 31 Similarly, both viruses could be used to coat a balloon or stent or be directly delivered to site of injury in the vessel to prevent intimal hyperplasia at the time of angioplasty and stenting. Furthermore, it might be advantageous to expose the vein to an agent at the time of arterial-venous fistula creation to prevent intimal hyperplasia in dialysis access patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2, 4 Furthermore, we have shown that we are able to modulate intimal hyperplasia in a relevant vein graft model. 17, 31 Similarly, both viruses could be used to coat a balloon or stent or be directly delivered to site of injury in the vessel to prevent intimal hyperplasia at the time of angioplasty and stenting. Furthermore, it might be advantageous to expose the vein to an agent at the time of arterial-venous fistula creation to prevent intimal hyperplasia in dialysis access patients.…”
Section: Discussionmentioning
confidence: 99%
“…After 2 h, the medium was replaced with supplemented growth medium and cultured for 72 h. HAOSMC viability was quantified with an MTT assay as previously described. 31 To determine if autocrine factors were responsible for the dose effect experiments were performed with conditioned media. Conditioned medium was prepared by first exposing HAOSMCs at >95% confluence in a T-25 to R3616 or R7020 at an MOI of 1 in M199V for 2 h. The media was then replaced with growth medium supplemented with 10% fetal bovine serum (5 ml) and cultured for 48 h. To remove viral particles the conditioned media was centrifuged at 40 000 r.p.m.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After 48, 72, 96 and 120 h of viral infection, live cells were measured by an MTT assay (Cell Proliferation Kit 1; Roche Diagnostics, Indianapolis, IN, USA) for cell viability according to the manufacturer's instructions. 36 LNCaP xenograft experiments Athymic nude mice were purchased from Harlan Sprague Dawley (Indianapolis, IN, USA) and LNCaP cancer cells were implanted subcutaneously by injecting 5 Â 10 6 cells in 100 ml of medium with matrigel at four different sites over the shoulders and hind legs on both sides. Animals were monitored for tumor development two times a week by palpation of the injection sites.…”
Section: Cell Viability Assaymentioning
confidence: 99%
“…Als Beispiel sei ein Gen-modifizierter Herpes-Simplex-Virus genannt, der zur Infektion von Eigenvenenpatches verwendet wurde. Dieser genetisch modifizierte Flicken konnte dann im Hundemodell eine Reduktion der Intimahyperplasie bewirken[11].All diese Techniken sind aufregend und viel versprechend. Der routinemäßige Einsatz steht jedoch noch nicht bevor.…”
unclassified